Multiple spacer sequence typing of Coxiella burnetii carried by ticks in Gansu, China - Xu, Ze-Yun; Wang, Fang-Ni; Jian, Rui; Xue, Jing; Guo, Ya-Chun; Guo, Wen-Ping (Frontiers in Veterinary Science, 2024)
BackgroundCoxiella burnetii is a zoonotic pathogen that causes Q fever and is found worldwide. Ticks serve as the primary reservoir, playing an important role in maintaining the natural cycle of C. burnetii. C. burnetii is transmitted to animals when ticks feed on their blood. However, information on C. burnetii infection in ticks remains limited, despite the widespread prevalence of the infection in humans and animals across China.MethodsIn this study, 192 engorged ticks were collected from Baiyin City of Gansu Province, China. The presence of Coxiella burnetii in ticks was specifically identified by detecting the IS1111 gene using nested polymerase chain reaction (nPCR). In addition, the 16S rRNA gene of C. burnetii was molecularly characterized using nPCR. A total of 10 spacer sequences (Cox 2, 5, 18, 20, 22, 37, 51, 56, 57, and 61) were amplified using PCR against positive specimens for MST analysis.ResultsAll collected ticks were identified as Hyalomma marginatum, and 90 of them tested positive for C. burnetii, with a positive rate of 46.9% (90/192). The 16S rRNA gene analysis showed that the novel C. burnetii variants detected in this study were closely related to other C. burnetii strains in the world. The allele codes found in the present study for loci Cox2-Cox5-Cox18-Cox20-Cox22-Cox37-Cox51-Cox56-Cox57-Cox61 were 8-4-9-5-7-5-2-3-11-6. This represents a novel combination of allele values, similar to MST28, currently designated as MST85 in the Multi Spacers Typing (MST) database.ConclusionOur results revealed the circulation of a novel MST genotype of C. burnetii in Baiyin City, Gansu Province, China. The detection of C. burnetii in ticks suggests a potential public health risk to the local human population.